The calculus of the gift: Money and social relationships in Japan - Katherine Rupp (economic sociology. perspectives and conversations, 2022)
Examination of Japanese gift practices leads to a deeper exploration of networks and social relationships in Japanese society, and, at the same time, to a more detailed understanding of processes of borrowing and transformation in the history of Asian cultural interchange. The study of Japanese gift-giving necessarily also engages with an established empirical and theoretical tradition in anthropology, a tradition that often appears unable to escape from certain assumptions generated by the peculiar place of gifts in European and American popular ideologies of social life.
Keywords: 300